THE REALIZATION OF SPEECH FUNCTION IN ONANG- ONANG - Linda Efrina Nasution; Busmin Gurning; Rahmad Husein (LINGUISTIK TERAPAN, 2019)
This study addresse analysis the realization of Speech Function in Onang- onang. The main objectives of this study was to investigate how the Speech Function were realized in Onang- onang. This study based on descriptive qualitative approach. The data were collected by applying documentary technique. The data were the utterances consisting of clauses in Onang – onang. The data were analyzed based on the theory of Speech Function proposed by Halliday, each of Speech Function found their realization in Mood. There were found 96 data of seven kinds of Onang- onang that realized in two kinds of Mood. The result of this study revealed that the Speech Function in Onang – onang were realized both in congruent and metaphorical realization in Mood. Keywords: Speech Function, Mood, Onang-onang, Realization